Taxing income or consumption: Macroeconomic and distributional effects for Italy - Diego D'Andria; Jason DeBacker; Richard W. Evans; Jonathan Pycroft; Magdalena Zachlod-Jelec (European Commission, Joint Research Centre (JRC), 2021)
We study a set of tax reforms introducing a budget-neutral tax shift in Italy, from labour income to consumption taxes. To this end we use a microsimulation model to provide the output with which to estimate the parameters of tax functions in an overlapping-generations computable general equilibrium model. In doing so we make marginal and average tax rates bivariate non-linear functions of capital income and labour income. The methodology allows for the representation of the non-linearities of the tax and social benefit system and interactions between capital and labour incomes. The linked macro model then simulates labour supply, consumption and savings in a dynamic setting, thus accounting for behavioural and general equilibrium effects within a life-cycle optimization framework. Our simulations show that a tax shift made by cutting personal income tax rates might bring significant efficiency gains in Italy, with limited regressive effects, notwithstanding the revenue-compensating increase in consumptions taxes.
Keywords: H24; H31; D15; D58; 330; computable general equilibrium; overlapping generations; taxation; microsimulation; Italy; tax shift